Malaysian sign language mobile app - Batrisyia, Rizal; Rassem, Taha H. (2021)
Mute and the deaf people cannot communicate with normal people easily. Sign language is a language that normally uses body movement to transport meaning by mute and deaf people. The body language includes the movement, orientation and shapes of hands, arms, body and facial expressions to express meaning. Sign language is difficult to understand and use. This application will translate the word that user has typed into Malaysian Sign Language gesture. The innovation in the project is to give a solution to easily communicate with mute and deaf people effectively.